PKM Pelatihan Komunikasi Dakwah Berbasis Religiolinguistik pada Pengurus Pusat Studi dan Dakwah Mahasiswa Muslim (PUSDAMM) FBS UNM: Pengabdian - Muhammad Saleh; Dedi Gunawan Saputra; Mayong (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This Community Service (PKM) aims to address the communication competency gaps in preaching faced by the administrators of the Center for Muslim Student Studies and Preaching (PUSDAMM) at FBS UNM amidst the currents of pluralism and the development of digital campus communication. The solution offered is training and mentoring. This activity is conducted using a proportional method consisting of Counseling, Exercise, Demonstration, and Simulation (each 25%), followed by Reflection. The results of this Community Service Program (PkM) resulted in the implementation of a Da'wah Communication Model based on Re-linguistic principles, which significantly improved partner competencies, as evidenced by the average score increasing from 62.5 to 88.9 in three aspects: expanded conceptual understanding, the ability to design persuasive and linguistically-based da'wah discourse, and the ability to apply the model in field practice. Overall, this activity successfully strengthened the capacity for polite, contextual, and productive da'wah communication, supporting the development of students' religious character.